Retarder suitable for temperature of 200 DEG C and preparation method thereof

By using a retarder composed of polymer copolymer and polymer chains grafted with inorganic nanoparticles under ultra-high temperature conditions at 200°C, the problems of insufficient thickening time, poor sedimentation stability and abnormal thickening curve were solved. The stable thickening effect is achieved in the range of 150℃ to 200℃, meeting the construction needs of high-temperature deep wells.

CN119463199APending Publication Date: 2025-02-18SICHUAN CHUANQING UNDERGROUND TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411324190.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Under ultra-high temperature conditions of 200°C, common retarders in cementing have problems such as insufficient thickening time, poor settling stability, abnormal thickening curves, and "inverted" of the thickening time and specific temperature ranges of the addition.

Method used

A retarder consisting of a polymer copolymer formed by copolymerization of multiple monomers (component I) and a polymer chain (component II) grafted with inorganic nanoparticles. Component II is formed on component I through the action of ultrasonic waves and initiator as side branches, forming a retarder with a special structure.

Benefits of technology

The retarder maintains good thickening time and flow in the interval of 150°C to 200°C. The thickening time and the specific temperature range of addition are good, avoiding the sudden drop in the thickening effect and satisfying high-temperature deep wells and complex wells construction requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463199A_ABST
    Figure CN119463199A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of oil and gas well exploitation auxiliary agents, and particularly discloses a retarder suitable for the temperature of 200 DEG C and a preparation method of the retarder. Wherein the component I is a high-molecular copolymer formed by copolymerizing a plurality of monomers, and the component II is a high-molecular chain grafted with inorganic nanoparticles; the component II is used as a side chain to be grafted on the component I through ultrasonic waves and the action of an initiator, so as to form the retarder; wherein the mass ratio of the component I to the component II is (0.5-1): (8-11). The cement paste has the beneficial effects that the fluidity and the thickening time of the cement paste within the interval of 150-200 DEG C have a good dosage linear relationship; the hydration rate is effectively reduced, the thickening time is prolonged, and the high-temperature stability is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of oil and gas well mining auxiliary agents, in particular to a retarder suitable for 200 DEG C and a preparation method thereof. Background Art

[0002] Oil is an important part of the energy industry. In recent years, as oil consumption continues to increase, the intensity of exploitation has also continued to rise. Shallow oil and gas reserves cannot meet demand, and new oil and gas can only be developed in deeper layers to meet demand. Therefore, more advanced exploitation technology is needed to exploit deep oil and gas to improve exploitation efficiency. At present, cementing at home and abroad mainly has problems such as safe pumping under high temperature and high pressure conditions, slow strength development of top cement stone during the waiting process, poor compatibility, and abnormal thickening curve. These problems lead to the cementing construction quality failing to meet requirements.

[0003] The research on retarders below 150°C is relatively mature. However, under ultra-high temperature conditions of 200°C, problems such as insufficient thickening time to reach the pumping position, poor settlement stability, abnormal phenomena such as "bulging" and "core" on the thickening curve, and "inversion" of the thickening time and the specific temperature range of the added amount often occur during cementing.

[0004] Common types of retarders include polymers, inorganic compounds, cellulose, and organic phosphonic acids. However, the temperature resistance of single-component retarders is poor. In high-temperature and high-pressure formation environments, due to molecular chain breakage and decomposition, they lose their ability to slow down the setting of the working fluid, thus causing engineering accidents. Summary of the invention

[0005] The purpose of the present invention is to overcome the shortcomings of the prior art, provide a retarder suitable for 200°C and a preparation method thereof, and solve the problems of insufficient thickening time and difficulty in reaching the pumping position, poor sedimentation stability, abnormal phenomena such as "bulging" and "centering" on the thickening curve, and "inversion" of the thickening time and the specific temperature range of the addition amount under ultra-high temperature conditions of 200°C in cementing.

[0006] The purpose of the present invention is achieved through the following technical solutions:

[0007] In the first aspect, the present application provides a retarder suitable for use at 200°C, comprising component I and component II; wherein component I is a polymer copolymer formed by copolymerization of multiple monomers, and component II is a polymer chain grafted with inorganic nanoparticles;

[0008] The component II is grafted onto the component I as a side chain through the action of ultrasound and an initiator to form a retarder; wherein the mass ratio of the component I to the component II is (0.5-1):(8-11).

[0009] In one embodiment of the present application, the component I is prepared by initiating a free radical polymerization reaction initiator of an aqueous solution with a first monomer, a second monomer, a third monomer and a fourth monomer; wherein the first monomer is an unsaturated sulfonic acid monomer, the second monomer is an unsaturated carboxylic acid monomer, the third monomer is an acrylamide monomer, and the fourth monomer is a macrocyclic side-group vinyl monomer, and the molar ratio of the four is (5-8): (2-5): (2-4): (1-2).

[0010] In one embodiment of the present application, the first monomer is one or two of sulfonic acid monomers such as styrene sulfonic acid, sodium propylene sulfonate, and sodium methpropylene sulfonate; the second monomer includes unsaturated carboxylic acid monomers such as acrylic acid, fumaric acid, and one or two of carboxylic acid monomers; the third monomer includes acrylamide, methacrylamide, N,N'-methylenebisacrylamide, N-(hydroxymethyl)-2-methyl-2-acrylamide, N-isopropylacrylamide, dimethylacrylamide, N-(N-butoxymethyl)acrylamide, acrylic acid morpholine, and N-(2-hydroxyethyl)acrylamide; the fourth monomer includes one or more of N-vinyl pyrrolidone, N-vinyl caprolactam, 1,5-cyclooctadiene-3-ethylene, 4-vinylcyclohexene, and cyclododecahexaene-1-ethylene monomers.

[0011] In one embodiment of the present application, the aqueous solution free radical polymerization reaction initiator is a redox initiator, which is selected from two of ammonium persulfate, ammonium sulfite, sodium bisulfite, and potassium persulfate, and is compounded in a mass ratio of 1:1; the aqueous solution free radical polymerization reaction initiator is 0.5% to 1% of the total weight of the four monomers: the first monomer, the second monomer, the third monomer, and the fourth monomer.

[0012] In one embodiment of the present application, in the component II: the polymer chain is prepared by initiating unsaturated sulfonic acid monomers and unsaturated cationic monomers with corresponding initiators; and the inorganic nanoparticles are grafted onto the polymer chain after being acted on by a silane coupling agent.

[0013] In one embodiment of the present application, the chemical formula of the silane coupling agent is RSiX 3 ; Wherein, X represents a hydrolyzable functional group, which can undergo coupling reaction with methoxy and ethoxy groups on inorganic materials; R represents an organic functional group, which can undergo coupling reaction with organic groups such as vinyl, ethoxy, and methacrylate.

[0014] In one embodiment of the present application, in the polymer chain of component II, the molar ratio of the unsaturated sulfonic acid monomer to the unsaturated cationic monomer is 3-5:3-6.

[0015] In one embodiment of the present application, in the polymer chain of component II, the unsaturated sulfonic acid monomer is one of 2-acrylamide-2-methylpropanesulfonic acid and 2-hydroxy-3-allylsulfonic acid, and the unsaturated cationic monomer is one of hexadecyldimethylpropyl methacrylamide ammonium bromide and 2-(methacryloyloxy)ethyltrimethylammonium chloride. The silane coupling agent is one of γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, γ-(methacryloyloxy)propyltrimethoxysilane, vinyltriethoxysilane, vinyltrimethoxysilane, and vinyltri(β-methoxyethoxy)silane. The nano-inorganic particles are one of nano-particles such as nano-titanium dioxide, nano-zinc oxide, nano-iron oxide, and nano-aluminum oxide, and the nano-particle content in the nano-particle material used, i.e., the purity is > 99%.

[0016] In one embodiment of the present application, when preparing the high-fraction chain of component II, the initiator used is one of azobisisobutyl ether hydrochloride or azobisisopropylimidazoline hydrochloride.

[0017] In a second aspect, the present application provides a method for preparing a retarder suitable for 200° C., comprising the following steps:

[0018] S1. Prepare component I;

[0019] Dissolve unsaturated sulfonic acid monomer A, unsaturated carboxylic acid monomer B, acrylamide monomer C and macrocyclic side vinyl monomer D in deionized water at a molar ratio of (5-8):(2-5):(2-4):(1-2) to form a mixed solution; the mass concentration of the four monomers in the mixed solution is 20%-25%;

[0020] The pH value of the mixed solution is adjusted to 2-3 to obtain an acidic mixed solution;

[0021] Then the acidic mixed solution is heated to 60°C to 70°C; the initiator is compounded and added to the heated acidic mixed solution at a drop rate of 3 to 4 seconds per drop; then the mixture is reacted at a constant temperature for a period of time to obtain a reacted solution;

[0022] The reaction solution is extracted with acetone or anhydrous ethanol and then further dried, or the reaction solution is directly ventilated and dried at a certain temperature; after drying, it is ground to finally obtain component I of the polymer copolymer.

[0023] S2. Prepare component II;

[0024] S201. The inorganic nanoparticles E are dissolved in deionized water and stirred thoroughly;

[0025] S202. Preparation of polymer chains;

[0026] Dissolving unsaturated sulfonic acid monomer F, unsaturated cationic monomer G and corresponding initiator in deionized water to obtain respective monomer solutions; then adding the three monomer solutions into a container in sequence to obtain a mixed monomer aqueous solution; in the mixed monomer aqueous solution, the mass concentration of unsaturated sulfonic acid monomer F and unsaturated cationic monomer G is 20% to 25%;

[0027] The mixed monomer fusion aqueous solution is heated to 50°C to 55°C, and stirred at a speed of 100 to 120 rpm; during the rotation, the corresponding initiator is added dropwise at a speed of 3 to 5 seconds per drop, and the mixture is reacted at a constant temperature for a period of time to obtain a polymer chain solution;

[0028] Then a chain transfer agent is added;

[0029] S203. The silane coupling agent H is added to the fully stirred solution in S201, and then mixed thoroughly; the fully mixed solution is added to the polymer chain solution in S202, and the reaction is continued for a period of time;

[0030] The solution after a period of reaction is extracted with acetone or anhydrous ethanol, further dried, and ground into powder to obtain the grafted side chain F-co-GgH(gE), that is, component II;

[0031] Wherein, E represents inorganic nanoparticles; F represents unsaturated sulfonic acid monomer; G represents unsaturated cationic monomer; H represents silane coupling agent; -co- represents copolymer; F-co-G represents that F and G form a copolymer; g represents grafting; F-co-GgH(gE) represents that E is connected to H by grafting to form H(gE), and H(gE) is grafted as a whole on the copolymer formed by F and G;

[0032] S3. Component II is grafted onto component I as a side chain;

[0033] Place component I in an ultrasonic machine and sonicate for a period of time;

[0034] Dissolve component II, the corresponding initiator, and component I after ultrasound in deionized water in different containers to obtain three corresponding solutions;

[0035] Then add the component II solution and the component I solution after ultrasonic treatment into a container, adjust the reaction temperature to 55°C to 65°C, then add the corresponding initiator solution dropwise within 15min to 20min, and then keep the temperature constant for a period of time;

[0036] The solution after a period of reaction is extracted with acetone or anhydrous ethanol, and the extract is placed in a drying oven for drying, and finally a retarder suitable for 200°C is obtained.

[0037] It should be noted that the chain transfer agent is preferably hydroxypropionic acid, but other types of chain transfer agents can also be used. Chain transfer agents are chemical substances used to control the molecular weight and molecular weight distribution of polymers. In free radical polymerization, chain transfer agents transfer active chain end free radicals to another molecule by reacting with the growing polymer chain, thereby terminating the growth of the current chain and starting a new growing chain. This process is called a chain transfer reaction. The main functions of chain transfer agents include: 1. Limiting the length of the polymer chain and controlling the molecular weight; 2. Adjusting the molecular weight distribution, reducing the difference in molecular chains in the polymer sample, and obtaining a narrower molecular weight distribution. This is crucial to the performance of component II.

[0038] For ease of understanding, this solution is further explained:

[0039] 1. In the component A of the high molecular polymer as the main chain:

[0040] Monomer A and monomer B, monomer C, monomer D and other raw materials are subjected to chemical polymerization reaction. The product is obtained by extraction with anhydrous ethanol or acetone or direct drying. The method has reliable principle, simple operation and can obtain a higher yield.

[0041] The molecular copolymer of component A uses monomers such as unsaturated sulfonic acid monomers, unsaturated carboxylic acid monomers and amide groups with adsorption capacity. The adsorption capacity of sulfonic acid groups and carboxylic acid groups is mainly derived from their polarity, acidity and ability to form hydrogen bonds. Sulfonic acid groups and carboxylic acid groups are both strongly acidic functional groups that can release protons (H + ), forming negative ions in aqueous solution, increasing the adsorption of metal ions and cations, and can effectively adsorb Ca in cement slurry 2+ and other hydrated particles. The amide group is a polar functional group. The carbonyl part (C=O) has a high electronegativity, while the amino part (NH 2 ) are relatively less electronegative, and this polarity difference helps to form adsorption with other polar molecules or ions. Macrocyclic vinyl monomers are beneficial to improve the rigidity and temperature resistance of high molecular copolymers.

[0042] 2. In component B as a side chain:

[0043] Component B is F-co-GgH(gE).

[0044] The side chain significantly improves the polymer performance by introducing cationic monomers. Cationic monomers enhance the adsorption of retarders and cement particles, especially under high temperature conditions, effectively preventing abnormal gelation and particle sedimentation of cement slurry, thereby improving the stability and pumpability of cement slurry. In addition, the appropriate increase in cationic content can also promote the development of early strength of cement slurry while ensuring that the strength of cement stone is not affected. This helps to improve rheological properties, enhance salt resistance, and broaden the application temperature range, making it more suitable for cementing operations in complex oil and gas wells such as deep wells and ultra-deep wells, and helps to improve cementing quality and operation efficiency.

[0045] Silane coupling agent is a kind of organic silicon monomer containing two different reactive groups, which can chemically bond with organic and inorganic materials, that is, couple. Its chemical formula is usually RSiX 3 , where X is in the silane coupling agent RSiX 3 represents a hydrolyzable group, and the general structure of X can be halogen (such as chlorine, bromine, etc.), alkoxy (such as methoxy-OCH 3 , ethoxy-OCH 2 CH 3 etc.), acyloxy (such as acetoxy-OCOCH 3 etc.) or other hydrolyzable functional groups. For example, in γ-aminopropyltriethoxysilane (NH 2 (CH 2 ) 3 Si(OCH 2 CH 3 ) 3 ) is an ethoxyl group (-OCH 2 CH 3 ); and γ-(methacryloyloxy)propyltrimethoxysilane (CH 2 =C(CH 3 )COO(CH 2 ) 3 Si(OCH 3 ) 3 ) is a methoxy group (-OCH 3 ). R represents an organic functional group, such as methacryloyloxy (CH 2 =C(CH 3 )COO), vinyl (CH 2 =CH), acrylate (CH 2 =CHCOOCH 2 =CHCOO), methacryloyloxypropoxy (CH 2 CH(OH)CH 2 OCH 2 CH(OH)CH 2O) and other groups provide active points for reaction with organic materials. In the present invention, silane coupling agent can improve the compatibility of inorganic nanoparticles and polymer materials. Two groups of silane coupling agent, one is combined with the bonded nano inorganic material, and the other is combined with the polymer material to form a strong chemical bond, thereby improving the rigidity and temperature resistance of the polymer chain.

[0046] 3. After grafting component B with side chain onto component A:

[0047] A comb-shaped macromolecule was constructed. The adsorption groups on its main chain and side chain can effectively form complexes with calcium ions in cement, thereby slowing down the hydration rate of cement. This effect can prolong the thickening time of cement slurry and improve its stability under high temperature conditions. At the same time, the adsorbent side chain can also effectively dilute the cement slurry, which is beneficial to the compatibility of the retarder with other admixtures. The inorganic nanoparticles on the grafted side chain can fill the pores of cement stone and improve the strength of cement stone, thereby solving the problem of slow strength development of cement stone. The retarder can meet the application requirements of oil well cement in high-temperature deep well cementing.

[0048] The present invention has the following advantages:

[0049] (1) The raw materials of the present invention are easily available, the polymerization reaction between the monomers is sufficient, the performance is stable and the conversion rate is high;

[0050] (2) The present invention has strong temperature resistance, can ensure the fluidity of cement slurry in the range of 150°C to 200°C, and the thickening time has a good linear relationship with the amount of cement added. The strength development of cement paste will not be affected in each temperature range, and the comprehensive performance is good, which meets the construction requirements of high-temperature deep wells and complex wells.

[0051] (3) The retarder of the present invention has good compatibility and compatibility with various admixtures, especially with polymer fluid loss additives and suspended solids stabilizers;

[0052] (4) The present invention innovatively designs a comb-shaped macromolecular retarder, whose adsorption groups on the main chain and side chain form complexes with calcium ions in cement, effectively slowing down the hydration rate, prolonging the thickening time, and improving high-temperature stability. The adsorption of the side chain also enhances the compatibility with other admixtures. Inorganic nanoparticles fill the pores of cement stone, improve strength, solve the problem of slow strength development, and meet the high-performance requirements of oil well cement in high-temperature deep well cementing. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] Figure 1 This is an infrared spectrum of the retarder component 1 prepared in Example 1 of the present invention;

[0054] Figure 2 This is an infrared spectrum of the retarder component 2 prepared in Example 1 of the present invention;

[0055] Figure 3 This is the infrared spectrum of the retarder prepared in Example 1 of the present invention;

[0056] Figure 4 The thickening curve of Example 1 of the present invention at 200°C-100MPa with a retarder dosage of 5% was prepared;

[0057] Figure 5 A thickening curve at 200°C-100 MPa with a retarder addition of 5% was prepared for Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0058] The present invention is further described below in conjunction with the accompanying drawings, but the protection scope of the present invention is not limited to the following description.

[0059] It should be noted that, in order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0060] At present, the temperature of retarders in oil wells is below 150°C, and the corresponding research and development and application are relatively mature. However, these retarders do not perform well enough under ultra-high temperature conditions of 200°C. The reason is that common types of retarders include polymers, inorganic compounds, cellulose, and organic phosphonic acids. However, the temperature resistance of single-component retarders is poor. In high-temperature and high-pressure formation environments, due to problems such as molecular chain breakage and decomposition, they lose the property of retarding the setting in the working fluid. Specifically, for example, during the cementing process, due to the loss of activity of the retarder, the cementing cement solidifies quickly, resulting in insufficient thickening time for the cement, making it difficult to pump the cement to the specified position by a pump, and the entire cement thickening curve shows abnormal phenomena such as "bulging" and "heart wrapping".

[0061] Of course, there are some relatively high temperature resistant coagulants on the market, which perform well in the initial stage - the cement thickens well and can maintain the cement thickening for a period of time, but the thickening effect decreases sharply with the extension of time. To this end, the present invention develops a retarder, which has a good linear relationship between the fluidity and thickening time of the slurry in the range of 150℃ to 200℃ - there will be no sudden drop in the thickening effect due to the increase in temperature and the extension of time, and the thickening effect is relatively stable, meeting the construction requirements of high-temperature deep wells and complex wells.

[0062] The basic idea of ​​the retarder provided by the present invention is: obtain component I of the retarder by free radical polymerization of aqueous solution, obtain component II by free radical polymerization of aqueous solution and chemical grafting of inorganic nanoparticles, and then use ultrasonic wave and initiator synergistically to graft component II as a side chain onto component I, thereby forming a retarder with a special structure. In addition, the preparation of component I requires a full and thorough reaction, and the preparation of component II also requires a full and thorough reaction.

[0063] On the one hand, this embodiment provides a retarder suitable for 200°C, including component I and component II; wherein component I is a high molecular copolymer formed by copolymerization of multiple monomers, and component II is a high molecular chain grafted with inorganic nanoparticles; component II is grafted onto component I as a side chain through the action of ultrasound and an initiator to form a retarder; wherein the mass ratio of component I to component II is (0.5-1):(8-11).

[0064] Component I is further described below.

[0065] Component I is prepared by initiating a free radical polymerization reaction initiator in aqueous solution with a first monomer, a second monomer, a third monomer and a fourth monomer; wherein the first monomer is an unsaturated sulfonic acid monomer, the second monomer is an unsaturated carboxylic acid monomer, the third monomer is an acrylamide monomer, and the fourth monomer is a macrocyclic side-group vinyl monomer, and the molar ratio of the four monomers is (5-8): (2-5): (2-4): (1-2).

[0066] In component I: the first monomer is one or two of styrene sulfonic acid, sodium propylene sulfonate, and sodium methpropylene sulfonate; the second monomer includes unsaturated carboxylic acid monomers, which are one or two of acrylic acid and fumaric acid; the third monomer includes acrylamide, methacrylamide, N,N'-methylenebisacrylamide, N-(hydroxymethyl)-2-methyl-2-acrylamide, N-isopropylacrylamide, dimethylacrylamide, N-(N-butoxymethyl)acrylamide, acrylic acid morpholine, and N-(2-hydroxyethyl)acrylamide; the fourth monomer includes one or more of N-vinyl pyrrolidone, N-vinyl caprolactam, 1,5-cyclooctadiene-3-ethylene, 4-vinylcyclohexene, and cyclododecahexaene-1-ethylene monomers.

[0067] When component II is grafted onto component I as a side chain through the action of ultrasound and an initiator, the initiator used is an aqueous solution free radical polymerization initiator, which is a redox initiator, and is selected from two of ammonium persulfate, ammonium sulfite, sodium bisulfite, and potassium persulfate, and is compounded in a mass ratio of 1:1; the aqueous solution free radical polymerization initiator is 0.5% to 1% of the total weight of the four monomers: the first monomer, the second monomer, the third monomer, and the fourth monomer.

[0068] Component II is further described below.

[0069] In component II: the polymer chain is prepared by initiating unsaturated sulfonic acid monomers and unsaturated cationic monomers through corresponding initiators; the inorganic nanoparticles are grafted onto the polymer chain after being acted on by a silane coupling agent.

[0070] In the polymer chain of component II, the molar ratio of the unsaturated sulfonic acid monomer to the unsaturated cationic monomer is 3-5:3-6.

[0071] In the polymer chain of component II, the unsaturated sulfonic acid monomer is one of 2-acrylamide-2-methylpropanesulfonic acid and 2-hydroxy-3-allylsulfonic acid; the unsaturated cationic monomer is one of hexadecyldimethylpropyl methacrylamide ammonium bromide and 2-(methacryloyloxy)ethyltrimethylammonium chloride; the silane coupling agent is one of γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, γ-(methacryloyloxy)propyltrimethoxysilane, vinyltriethoxysilane, vinyltrimethoxysilane, and vinyltri(β-methoxyethoxy)silane; the nano-inorganic particles are one of nano-titanium dioxide, nano-zinc oxide, nano-iron oxide, and nano-aluminum oxide; and the nano-particle content, i.e., purity, of the nano-particle material used is greater than 99%.

[0072] In the preparation of component II, the chemical formula of the silane coupling agent is RSiX 3 ; Wherein, X represents a hydrolyzable functional group, which can undergo coupling reaction with methoxy and ethoxy groups on inorganic materials; R represents an organic functional group, which can undergo coupling reaction with organic groups such as vinyl, ethoxy, and methacrylate.

[0073] When preparing the high molecular weight chain of component II, the initiator used is one of azobisisobutyl ether hydrochloride and azobisisopropylimidazoline hydrochloride.

[0074] On the other hand, this embodiment discloses a method for preparing a retarder suitable for 200° C., comprising the following steps:

[0075] S1. Prepare component I;

[0076] Dissolve unsaturated sulfonic acid monomer A, unsaturated carboxylic acid monomer B, acrylamide monomer C and macrocyclic side vinyl monomer D in deionized water at a molar ratio of (5-8):(2-5):(2-4):(1-2) to form a mixed solution; the mass concentration of the four monomers in the mixed solution is 20%-25%;

[0077] The pH value of the mixed solution is adjusted to 2-3 to obtain an acidic mixed solution;

[0078] Then the acidic mixed solution is heated to 60°C to 70°C; the initiator is compounded and added to the heated acidic mixed solution at a drop rate of 3 to 4 seconds per drop; then the mixture is reacted at a constant temperature for a period of time to obtain a reacted solution;

[0079] The reaction solution is extracted with acetone or anhydrous ethanol and then further dried, or the reaction solution is directly ventilated and dried at a certain temperature; after drying, it is ground to finally obtain component I of the polymer copolymer.

[0080] S2. Prepare component II;

[0081] S201. The inorganic nanoparticles E are dissolved in deionized water and stirred thoroughly;

[0082] S202. Preparation of polymer chains;

[0083] Dissolving unsaturated sulfonic acid monomer F, unsaturated cationic monomer G and corresponding initiator in deionized water to obtain respective monomer solutions; then adding the three monomer solutions into a container in sequence to obtain a mixed monomer aqueous solution; in the mixed monomer aqueous solution, the mass concentration of unsaturated sulfonic acid monomer F and unsaturated cationic monomer G is 20% to 25%;

[0084] The mixed monomer fusion aqueous solution is heated to 50°C to 55°C, and stirred at a speed of 100 to 120 rpm; during the rotation, the corresponding initiator is added dropwise at a speed of 3 to 5 seconds per drop, and the mixture is reacted at a constant temperature for a period of time to obtain a polymer chain solution;

[0085] Then a chain transfer agent is added;

[0086] S203. The silane coupling agent H is added to the fully stirred solution in S201, and then mixed thoroughly; the fully mixed solution is added to the polymer chain solution in S202, and the reaction is continued for a period of time;

[0087] The solution after a period of reaction is extracted with acetone or anhydrous ethanol, further dried, and ground into powder to obtain the grafted side chain F-co-GgH(gE), that is, component II;

[0088] Wherein, E represents inorganic nanoparticles; F represents unsaturated sulfonic acid monomer; G represents unsaturated cationic monomer; H represents silane coupling agent; -co- represents copolymer; F-co-G represents that F and G form a copolymer; g represents grafting; F-co-GgH(gE) represents that E is connected to H by grafting to form H(gE), and H(gE) is grafted as a whole on the copolymer formed by F and G;

[0089] S3. Component II is grafted onto component I as a side chain;

[0090] Place component I in an ultrasonic machine and sonicate for a period of time;

[0091] Dissolve component II, the corresponding initiator, and component I after ultrasound in deionized water in different containers to obtain three corresponding solutions;

[0092] Then add the component II solution and the component I solution after ultrasonic treatment into a container, adjust the reaction temperature to 55°C to 65°C, then add the corresponding initiator solution dropwise within 15min to 20min, and then keep the temperature constant for a period of time;

[0093] The solution after a period of reaction is extracted with acetone or anhydrous ethanol, and the extract is placed in a drying oven for drying, and finally a retarder suitable for 200°C is obtained.

[0094] For ease of understanding, the present invention is further described below in conjunction with specific examples. However, the selection of components and proportions in the following examples is only for illustration and should not be used to limit the present invention.

[0095] (Example 1)

[0096] Example 1

[0097] Suitable for the preparation of 200℃ retarder.

[0098] Component 1: Styrene sulfonic acid, fumaric acid, acrylamide and N-vinyl pyrrolidone are mixed in a certain molar ratio and dissolved in deionized water to form a solution with a mass concentration of 20%. The ratio is styrene sulfonic acid: fumaric acid: acrylamide: N-vinyl pyrrolidone = 5:3:2:1. Then, the pH value of the solution is adjusted to 2. Under the condition of 60°C, the initiator ammonium persulfate and ammonium sulfite are compounded and dissolved in deionized water in a ratio of 1:1, and the initiator concentration is 1%. It is added to the mixed solution at a rate of 1 drop per 3 to 4 seconds, and the reaction is carried out at a constant temperature for 4 hours. Finally, the component 1 solution is extracted with acetone, further dried and ground into powder to obtain a poly (ethylene sulfonic acid, fumaric acid, acrylamide and N-vinyl pyrrolidone) polymer copolymer, the retarder component 1.

[0099] Component 2: First, dissolve nano zinc oxide in deionized water and stir mechanically for 24 hours. Then, dissolve 2-acrylamide-2-methylpropanesulfonic acid, hexadecyl dimethylpropyl methacrylamide ammonium bromide and azobisisobutyl ether hydrochloride in deionized water respectively, and add the monomer solution into a three-necked flask to form a uniform mixed aqueous solution with a mass concentration of 20%. At 50°C, stir at a rate of 100 revolutions per minute and begin to drip an initiator aqueous solution, the initiator concentration is 1%, and the dripping rate is controlled at 1 drop per 3 to 5 seconds. After constant temperature reaction for 1.5 hours, add hydroxypropionic acid. Add γ-aminopropyl triethoxysilane to the solution containing nano zinc oxide, mix well, pour into the above monomer solution and continue to react for 4 hours. Finally, extract the reaction solution with acetone, further dry and grind into powder to obtain the desired grafted side chain copolymer, retarder component 2.

[0100] The polymer copolymer component 1 was placed in an ultrasonic machine for ultrasonic treatment for 30 minutes. Subsequently, the ultrasonicated component 1, component 2 and benzoyl peroxide were dissolved in deionized water, and the component solutions were added to a three-necked flask, with a mass ratio of component 1 to component 2 of 0.5:8. At a reaction temperature of 55-65°C, the initiator aqueous solution was added dropwise within 15-20 minutes, the dropwise rate was maintained at 1 drop per 2-3 seconds, and the isothermal reaction was carried out for 4 hours. Finally, the reaction solution was extracted with acetone and further dried in a drying oven to obtain the desired retarder.

[0101] (Example 2)

[0102] Suitable for the preparation of 200℃ retarder.

[0103] Component 1: Sodium propylene sulfonate, acrylic acid, methacrylamide and N-vinyl pyrrolidone are mixed in a certain molar ratio and dissolved in deionized water to form a solution with a mass concentration of 20%. The ratio is sodium propylene sulfonate: acrylic acid: methacrylamide: N-vinyl pyrrolidone = 5:4:2:1. Then, the pH value of the solution is adjusted to 2. Under the condition of 65°C, the initiators ammonium persulfate and potassium persulfate are compounded and dissolved in deionized water in a ratio of 1:1, and the initiator concentration is 1%. It is added to the mixed solution at a rate of 1 drop per 3 to 4 seconds, and the reaction is carried out at a constant temperature for 4 hours. Finally, the component 1 solution is extracted with acetone, further dried and ground into powder to obtain a poly (sodium sulfonate, acrylic acid, methacrylamide and N-vinyl pyrrolidone) polymer copolymer, retarder component 1.

[0104] Component 2: First, dissolve the nano-iron oxide in deionized water and stir mechanically for 24 hours. Then, dissolve 2-acrylamide-2-methylpropanesulfonic acid, hexadecyl dimethylpropyl methacrylamide ammonium bromide and azobisisobutyl ether hydrochloride in deionized water respectively, and add the monomer solution into a three-necked flask to form a uniform mixed aqueous solution with a mass concentration of 20%. At 50°C, stir at a rate of 100 revolutions per minute and begin to drip the initiator aqueous solution, the initiator concentration is 1%, and the dripping rate is controlled at 1 drop per 3 to 5 seconds. After constant temperature reaction for 1.5 hours, add hydroxypropionic acid. Add γ-aminopropyl triethoxysilane to the solution containing nano-zinc oxide, mix well, pour into the above monomer solution and continue to react for 4 hours. Finally, extract the reaction solution with acetone, further dry and grind into powder to obtain the desired grafted side chain copolymer, retarder component 2.

[0105] The polymer copolymer component 1 was placed in an ultrasonic machine for ultrasonic treatment for 30 minutes. Subsequently, the ultrasonicated component 1, component 2 and benzoyl peroxide were dissolved in deionized water, and the component solutions were added to a three-necked flask, with a mass ratio of component 1 to component 2 of 1:11. At a reaction temperature of 55-65°C, the initiator aqueous solution was added dropwise within 15-20 minutes, the dropwise rate was maintained at 1 drop per 2-3 seconds, and the isothermal reaction was carried out for 4 hours. Finally, the reaction solution was extracted with acetone and further dried in a drying oven to obtain the desired retarder.

[0106] (Example 3)

[0107] Suitable for the preparation of 200℃ retarder.

[0108] Component 1: Sodium methacrylic acid, fumaric acid, acrylamide and N-vinyl pyrrolidone are mixed in a certain molar ratio and dissolved in deionized water to form a solution with a mass concentration of 20%. The ratio is sodium methacrylic acid: fumaric acid: acrylamide: N-vinyl pyrrolidone = 5:3:2:1. Then, the pH value of the solution is adjusted to 2. Under the condition of 60°C, the initiator ammonium persulfate and sodium bisulfite are compounded and dissolved in deionized water in a ratio of 1:1, and the initiator concentration is 0.9%. It is added to the mixed solution at a rate of 1 drop per 3 to 4 seconds, and the reaction is carried out at a constant temperature for 4 hours. Finally, the component 1 solution is extracted with acetone, further dried and ground into powder to obtain a poly (sodium methacrylic acid, fumaric acid, acrylamide and N-vinyl pyrrolidone) polymer copolymer, retarder component 1.

[0109] Component 2: First, dissolve the nano-iron oxide in deionized water and stir mechanically for 24 hours. Then, dissolve 2-hydroxy-3-allyl sulfonic acid, hexadecyl dimethylpropyl methacrylamide ammonium bromide and azodiisopropyl imidazoline hydrochloride in deionized water respectively, and add the monomer solution into a three-necked flask to form a uniform mixed aqueous solution with a mass concentration of 20%. At 50°C, stir at a rate of 100 revolutions per minute and begin to drip the initiator aqueous solution, the initiator concentration is 1%, the dripping rate is controlled at 1 drop per 3 to 5 seconds, and the reaction is kept at a constant temperature for 1.5 hours. Subsequently, hydroxypropionic acid is added. γ-(methacryloyloxy)propyltrimethoxysilane is added to the solution containing nano-zinc oxide, mixed evenly, and poured into the above monomer solution to continue the reaction for 4 hours. Finally, the reaction solution is extracted with acetone, further dried and ground into powder to obtain the desired grafted side chain copolymer, retarder component 2.

[0110] The polymer copolymer component 1 was placed in an ultrasonic machine for ultrasonic treatment for 30 minutes. Subsequently, the ultrasonicated component 1, component 2 and benzoyl peroxide were dissolved in deionized water, and the component solutions were added to a three-necked flask, with a mass ratio of component 1 to component 2 of 1:10. At a reaction temperature of 55-65°C, the initiator aqueous solution was added dropwise within 15-20 minutes, the dropwise rate was maintained at 1 drop per 2-3 seconds, and the isothermal reaction was carried out for 4 hours. Finally, the reaction solution was extracted with acetone and further dried in a drying oven to obtain the desired retarder.

[0111] (Example 4)

[0112] Suitable for the preparation of 200℃ retarder.

[0113] Component 1: Styrene sulfonic acid, fumaric acid, acrylamide and N-vinyl caprolactam are mixed in a certain molar ratio and dissolved in deionized water to form a solution with a mass concentration of 25%. The ratio is styrene sulfonic acid: fumaric acid: acrylamide: N-vinyl caprolactam = 5:3:2:2. Then, the pH value of the solution is adjusted to 2. Under the condition of 60°C, the initiator ammonium persulfate and ammonium sulfite are compounded and dissolved in deionized water in a ratio of 1:1, and the initiator concentration is 1%. It is added to the mixed solution at a rate of 1 drop per 3 to 4 seconds, and the reaction is carried out at a constant temperature for 4 hours. Finally, the component 1 solution is extracted with acetone, further dried and ground into powder to obtain a poly (ethylene sulfonic acid, fumaric acid, acrylamide and N-vinyl caprolactam) polymer copolymer, retarder component 1.

[0114] Component 2: First, dissolve nano zinc oxide in deionized water and stir mechanically for 24 hours. Then, dissolve 2-acrylamide-2-methylpropanesulfonic acid, hexadecyl dimethylpropyl methacrylamide ammonium bromide and azobisisobutyl ether hydrochloride in deionized water respectively, and add the monomer solution into a three-necked flask to form a uniform mixed aqueous solution with a mass concentration of 20%. At 50°C, stir at a rate of 100 revolutions per minute and begin to drip an initiator aqueous solution, the initiator concentration is 1%, the dripping rate is controlled at 1 drop per 3 to 5 seconds, and the reaction is kept at a constant temperature for 1.5 hours. Subsequently, hydroxypropionic acid is added. γ-aminopropyl triethoxysilane is added to the solution containing nano zinc oxide, mixed evenly, and poured into the above monomer solution to continue the reaction for 4 hours. Finally, the reaction solution is extracted with acetone, further dried and ground into powder to obtain the desired grafted side chain copolymer, retarder component 2.

[0115] The polymer copolymer component 1 was placed in an ultrasonic machine for ultrasonic treatment for 30 minutes. Subsequently, the ultrasonicated component 1, component 2 and tert-butyl peroxide were dissolved in deionized water, and the component solution was added to the three-necked flask with a mass ratio of component 1 to component 2 of 1:9. At a reaction temperature of 55-65°C, the initiator aqueous solution was added dropwise within 15-20 minutes, and the dropwise rate was maintained at 1 drop per 2-3 seconds, and the isothermal reaction was carried out for 4 hours. Finally, the reaction solution was extracted with acetone and further dried in a drying oven to obtain the desired retarder.

[0116] (Comparative Example 1)

[0117] Preparation of retarder.

[0118] Styrene sulfonic acid, fumaric acid, acrylamide and N-vinyl pyrrolidone are mixed in a certain molar ratio and dissolved in deionized water to form a solution with a mass concentration of 20%. The ratio is styrene sulfonic acid: fumaric acid: acrylamide: N-vinyl pyrrolidone = 5:3:2:1. Then, the pH value of the solution is adjusted to 2. At 60°C, the initiators ammonium persulfate and ammonium sulfite are compounded and dissolved in deionized water in a ratio of 1:1, and the initiator concentration is 1%. It is added to the mixed solution at a rate of 1 drop per 3 to 4 seconds, and the reaction is carried out at a constant temperature for 4 hours. Finally, the polymer solution is extracted with acetone, further dried and ground into powder to obtain a poly (styrene sulfonic acid, fumaric acid, acrylamide and N-vinyl pyrrolidone) polymer copolymer. The linear polymer is directly used as a retarder.

[0119] (Comparative Example 2)

[0120] Preparation of retarder.

[0121] Component 1: Styrene sulfonic acid, fumaric acid, acrylamide and N-vinyl caprolactam are mixed in a certain molar ratio and dissolved in deionized water to form a solution with a mass concentration of 25%. The ratio is styrene sulfonic acid: fumaric acid: acrylamide: N-vinyl caprolactam = 5:3:2:2. Then, the pH value of the solution is adjusted to 2. Under the condition of 60°C, the initiator ammonium persulfate and ammonium sulfite are compounded and dissolved in deionized water in a ratio of 1:1, and the initiator concentration is 1%. It is added to the mixed solution at a rate of 1 drop per 3 to 4 seconds, and the reaction is carried out at a constant temperature for 4 hours. Finally, the component 1 solution is extracted with acetone, further dried and ground into powder to obtain a poly (ethylene sulfonic acid, fumaric acid, acrylamide and N-vinyl caprolactam) polymer copolymer, retarder component 1.

[0122] Component 2: First, dissolve nano zinc oxide in deionized water and stir mechanically for 24 hours. Then, dissolve 2-acrylamide-2-methylpropanesulfonic acid, hexadecyl dimethylpropyl methacrylamide ammonium bromide and azobisisobutyl ether hydrochloride in deionized water respectively, and add the monomer solution into a three-necked flask to form a uniform mixed aqueous solution with a mass concentration of 20%. At 50°C, stir at a rate of 100 revolutions per minute and begin to drip an initiator aqueous solution, the initiator concentration is 1%, the dripping rate is controlled at 1 drop per 3 to 5 seconds, and the reaction is kept at a constant temperature for 1.5 hours. Subsequently, hydroxypropionic acid is added. γ-aminopropyl triethoxysilane is added to the solution containing nano zinc oxide, mixed evenly, and poured into the above monomer solution to continue the reaction for 4 hours. Finally, the reaction solution is extracted with acetone, further dried and ground into powder to obtain the desired grafted side chain copolymer, retarder component 2.

[0123] Dissolve component 1, component 2 and di-tert-butyl peroxide in deionized water respectively, and add the component solution into a three-necked flask with a mass ratio of component 1 to component 2 of 1:9. At a reaction temperature of 55-65°C, complete the dripping of the initiator aqueous solution within 15-20 minutes, maintain the dripping rate at 1 drop per 2-3 seconds, and carry out constant temperature reaction for 4 hours. Finally, extract the reaction solution with acetone and further dry it in a drying oven to obtain a retarder.

[0124] (Comparative Example 3)

[0125] Preparation of retarder.

[0126] Component 1: Styrene sulfonic acid, fumaric acid, acrylamide and N-vinyl pyrrolidone are mixed in a certain molar ratio and dissolved in deionized water to form a solution with a mass concentration of 20%. The ratio is styrene sulfonic acid: fumaric acid: acrylamide: N-vinyl pyrrolidone = 5:3:2:1. Then, the pH value of the solution is adjusted to 2. Under the condition of 60°C, the initiator ammonium persulfate and ammonium sulfite are compounded and dissolved in deionized water in a ratio of 1:1, and the initiator concentration is 1%. It is added to the mixed solution at a rate of 1 drop per 3 to 4 seconds, and the reaction is carried out at a constant temperature for 4 hours. Finally, the component 1 solution is extracted with acetone, further dried and ground into powder to obtain a poly (ethylene sulfonic acid, fumaric acid, acrylamide and N-vinyl pyrrolidone) polymer copolymer, the retarder component 1.

[0127] Component 2: Dissolve 2-acrylamide-2-methylpropanesulfonic acid, hexadecyl dimethylpropyl methacrylamide ammonium bromide and azobisisobutyl ether hydrochloride in deionized water respectively, add the monomer solution into a three-necked flask to form a uniform mixed aqueous solution with a mass concentration of 20%. At 50°C, stir at a rate of 100 revolutions per minute and begin to drip an initiator aqueous solution, the initiator concentration is 1%, and the dripping rate is controlled at 1 drop per 3 to 5 seconds. After constant temperature reaction for 1.5 hours, add hydroxypropionic acid and continue to react for 4 hours. Finally, extract the reaction solution with acetone, further dry and grind into powder to obtain the desired grafted side chain copolymer, retarder component 2.

[0128] The polymer copolymer component 1 was placed in an ultrasonic machine for ultrasonic treatment for 30 minutes. Subsequently, the ultrasonicated component 1, component 2 and benzoyl peroxide were dissolved in deionized water, and the component solutions were added to a three-necked flask, with a mass ratio of component 1 to component 2 of 0.5:8. At a reaction temperature of 55-65°C, the initiator aqueous solution was added dropwise within 15-20 minutes, the dropwise rate was maintained at 1 drop per 2-3 seconds, and the isothermal reaction was carried out for 4 hours. Finally, the reaction solution was extracted with acetone and further dried in a drying oven to obtain the desired retarder.

[0129] Performance Testing

[0130] The infrared absorption spectra of component 1, component 2 and retarder prepared in Example 1 were tested by FTIR infrared spectroscopy. The infrared absorption spectrum of component 1 prepared in Example 1 of the present invention is as follows: Figure 1 As shown, the infrared absorption spectrum of component 2 prepared in Example 1 of the present invention is as follows Figure 2 As shown, the infrared absorption spectrum of the retarder prepared in Example 1 of the present invention is as follows Figure 3 As shown. Figures 1 to 3From the characteristic peaks of each group, it can be seen that component 1 contains sulfonic acid group, carboxyl group, amide group and carbonyl group, indicating that component 1 is the target polymerization product; component 2 contains sulfonic acid group, amide group and modified silicon oxygen bond, indicating that component 2 is the target product; the retarder contains sulfonic acid group, carboxyl group, amide group, carbonyl group and modified silicon oxygen bond.

[0131] The retarders obtained by using different embodiments were evaluated, and the properties such as thickening time, fluidity, and water loss were measured at 200°C. The results are shown in Table 1. Cement slurry basic formula: Jiahua G-grade oil well cement + 50% quartz sand + 1% dispersant (USZ) + 5% fluid loss reducer (SD12) + X% retarder + 1.5% suspension stabilizer (SD89) + water, wherein the mass percentages of the components are calculated based on the weight of Jiahua G-grade oil well cement.

[0132] Table 1 Basic performance of different implementations at 200°C

[0133]

[0134]

[0135] The retarders obtained by using different embodiments were evaluated, and the compressive strength was measured at 150°C. The results are shown in Table 1. Cement slurry basic formula: Jiahua G-grade oil well cement + 50% quartz sand + 1% dispersant (USZ) + 5% fluid loss reducer (SD12) + X% retarder + 1.5% suspension stabilizer (SD89) + water, wherein the mass percentages of the components are calculated based on the weight of Jiahua G-grade oil well cement.

[0136] Table 2 Compressive strength and suspension stability of different embodiments at 150°C

[0137]

[0138] It can be seen from Table 1 that from Example 1 to Example 4, under different retarder dosages, the thickening curves are normal, and the thickening time is prolonged as the dosage is increased; in contrast, in Comparative Example 1, as the amount of retarder is increased, the curve shows core-encapsulation and bulging phenomena, and the compatibility with the dehydrating agent is not good, and the water loss increases from 65ml to 93ml; in Comparative Example 2, as the amount of retarder is increased, the thickening time is not obviously prolonged, the linear relationship is poor, and it is accompanied by the core-encapsulation phenomenon; in Comparative Example 3, when the retarder is added to 5%, the thickening time is 313min, and the extension time of cement slurry thickening is short. As the amount of retarder is increased, the water loss increases from 39 to 56, and the water loss is high.

[0139] It can be seen from Table 2 that: from Example 1 to Example 4, the 72h strength development is faster, and the settlement stability is good after curing at 150°C; for Comparative Example 1 and Comparative Example 3, the 72h strength development is slower, but the settlement stability of Comparative Example 3 is relatively good, and the strength development of Comparative Example 2 is normal but the settlement stability is poor.

[0140] The above embodiments only express preferred implementation modes, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present invention. It should be pointed out that, for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention.

Claims

1. A retarder suitable for 200°C, characterized in that: It comprises component I and component II; wherein component I is a polymer copolymer formed by copolymerization of multiple monomers, and component II is a polymer chain grafted with inorganic nanoparticles; The component II is grafted onto the component I as a side chain through the action of ultrasound and an initiator to form a retarder; wherein the mass ratio of the component I to the component II is (0.5-1):(8-11).

2. A retarder suitable for 200°C according to claim 1, characterized in that: The component I is prepared by initiating the first monomer, the second monomer, the third monomer and the fourth monomer with an aqueous solution free radical polymerization initiator; Among them, the first monomer is an unsaturated sulfonic acid monomer, the second monomer is an unsaturated carboxylic acid monomer, the third monomer is an acrylamide monomer, and the fourth monomer is a macrocyclic side-group vinyl monomer, and the molar ratio of the four monomers is (5-8): (2-5): (2-4): (1-2).

3. A retarder suitable for 200°C according to claim 2, characterized in that: The first monomer is one or two of styrene sulfonic acid, sodium propylene sulfonate, and sodium methyl propylene sulfonate; The second type of monomers include unsaturated carboxylic acid monomers, which are one or two of acrylic acid and fumaric acid; The third type of monomers include one or two of acrylamide, methacrylamide, N,N'-methylenebisacrylamide, N-(hydroxymethyl)-2-methyl-2-acrylamide, N-isopropylacrylamide, dimethylacrylamide, N-(N-butoxymethyl)acrylamide, morpholine acrylate, and N-(2-hydroxyethyl)acrylamide; The fourth type of monomers include one or more of N-vinyl pyrrolidone, N-vinyl caprolactam, 1,5-cyclooctadiene-3-ethylene, 4-vinyl cyclohexene, and cyclododecahexaene-1-ethylene monomers.

4. A retarder suitable for 200°C according to claim 2, characterized in that: The aqueous solution free radical polymerization initiator is a redox initiator, which is selected from ammonium persulfate, ammonium sulfite, sodium bisulfite, and potassium persulfate, and is compounded in a mass ratio of 1:1; The aqueous solution free radical polymerization initiator is 0.5% to 1% of the total weight of the first monomer, the second monomer, the third monomer and the fourth monomer.

5. A retarder suitable for 200°C and a preparation method thereof according to any one of claims 1 to 4, characterized in that: In the component II: the polymer chain is prepared by initiating unsaturated sulfonic acid monomers and unsaturated cationic monomers with corresponding initiators; the inorganic nanoparticles are grafted onto the polymer chain after being acted on by a silane coupling agent.

6. A retarder suitable for 200°C according to claim 5, characterized in that: The chemical formula of the silane coupling agent is RSiX3; wherein X represents a hydrolyzable functional group, which can undergo coupling reaction with methoxy and ethoxy groups on inorganic materials; and R represents an organic functional group, which can undergo coupling reaction with organic groups such as vinyl, ethoxy and methacrylate.

7. A retarder suitable for 200°C according to claim 6, characterized in that: In the polymer chain of component II, the molar ratio of unsaturated sulfonic acid monomer to unsaturated cationic monomer is 3-5:3-6.

8. A retarder suitable for 200°C according to claim 6 or 7, characterized in that: In the polymer chain of component II, the unsaturated sulfonic acid monomer is one of 2-acrylamide-2-methylpropanesulfonic acid and 2-hydroxy-3-allylsulfonic acid, and the unsaturated cationic monomer is one of hexadecyldimethylpropylmethacrylamideammonium bromide and 2-(methacryloyloxy)ethyltrimethylammonium chloride; The silane coupling agent is one of γ-aminopropyl triethoxysilane, γ-glycidyloxypropyl trimethoxysilane, γ-(methacryloyloxy)propyl trimethoxysilane, vinyl triethoxysilane, vinyl trimethoxysilane, and vinyl tri(β-methoxyethoxy)silane; The nano inorganic particles are one of nano titanium dioxide, nano zinc oxide, nano iron oxide and nano aluminum oxide. The nano particle content in the nano particle material used, namely, the purity is greater than 99%.

9. A retarder suitable for 200°C according to claim 8, characterized in that: When the high molecular weight chain of component II is prepared, the initiator used is one of azobisisobutyl ether hydrochloride and azobisisopropylimidazoline hydrochloride.

10. A method for preparing a retarder suitable for 200°C, characterized in that: The following steps are involved: S1. Prepare component I; Dissolve unsaturated sulfonic acid monomer A, unsaturated carboxylic acid monomer B, acrylamide monomer C and macrocyclic side vinyl monomer D in deionized water at a molar ratio of (5-8):(2-5):(2-4):(1-2) to form a mixed solution; the mass concentration of the four monomers in the mixed solution is 20%-25%; The pH value of the mixed solution is adjusted to 2-3 to obtain an acidic mixed solution; Then the acidic mixed solution is heated to 60°C to 70°C; the initiator is compounded and added to the heated acidic mixed solution at a drop rate of 3 to 4 seconds per drop; then the mixture is reacted at a constant temperature for a period of time to obtain a reacted solution; The reaction solution is extracted with acetone or anhydrous ethanol and then further dried, or the reaction solution is directly ventilated and dried at a certain temperature; after drying, it is ground to finally obtain component I of the polymer copolymer. S2. Prepare component II; S201. The inorganic nanoparticles E are dissolved in deionized water and stirred thoroughly; S202. Preparation of polymer chains; Dissolving unsaturated sulfonic acid monomer F, unsaturated cationic monomer G and corresponding initiator in deionized water to obtain respective monomer solutions; then adding the three monomer solutions into a container in sequence to obtain a mixed monomer aqueous solution; in the mixed monomer aqueous solution, the mass concentration of unsaturated sulfonic acid monomer F and unsaturated cationic monomer G is 20% to 25%; The mixed monomer fusion aqueous solution is heated to 50°C to 55°C, and stirred at a speed of 100 to 120 rpm; during the rotation, the corresponding initiator is added dropwise at a speed of 3 to 5 seconds per drop, and the mixture is reacted at a constant temperature for a period of time to obtain a polymer chain solution; Then a chain transfer agent is added; S203. The silane coupling agent H is added to the fully stirred solution in S201, and then mixed thoroughly; the fully mixed solution is added to the polymer chain solution in S202, and the reaction is continued for a period of time; The solution after a period of reaction is extracted with acetone or anhydrous ethanol, further dried, and ground into powder to obtain the grafted side chain F-co-GgH(gE), that is, component II; Wherein, E represents inorganic nanoparticles; F represents unsaturated sulfonic acid monomer; G represents unsaturated cationic monomer; H represents silane coupling agent; -co- represents copolymer; F-co-G represents that F and G form a copolymer; g represents grafting; F-co-GgH(gE) represents that E is connected to H by grafting to form H(gE), and H(gE) is grafted as a whole on the copolymer formed by F and G; S3. Component II is grafted onto component I as a side chain; Place component I in an ultrasonic machine and sonicate for a period of time; Dissolve component II, the corresponding initiator, and component I after ultrasound in deionized water in different containers to obtain three corresponding solutions; Then add the component II solution and the component I solution after ultrasonic treatment into a container, adjust the reaction temperature to 55°C to 65°C, then add the corresponding initiator solution dropwise within 15min to 20min, and then keep the temperature constant for a period of time; The solution after a period of reaction is extracted with acetone or anhydrous ethanol, and the extract is placed in a drying oven for drying, and finally a retarder suitable for 200°C is obtained.